Εφαρμογή παρακολούθησης χρήσης κινητού τηλεφώνου σε πλατφόρμα Android. - Κοζομπόλης, Νικόλαος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών, 2016)
The purpose of this thesis, titled "Android smartphone application for utilization monitoring", is the development of an application for Android smartphones that audits the consumption of prepaid voice calls, sms and mobile data on behalf of the user. The application monitors the usage locally and , at certain intervals, confirms the measurements by sending an automated text message to the provider. The graphic interface of the application was designed as to provide uninterupted balance monitoring and minimize the customer's physical and mental effort.